Insulin Glargine U-300 in Type 1 Diabetes Mellitus: Single-Center Experience - Özge POLAT KORKMAZ; Zeynep OŞAR SİVA (Namık Kemal Tıp Dergisi, 2025)
Aim: This study aimed to evaluate the clinical outcomes of switching from first-generation basal insulins to insulin glargine U-300 (Gla-300) in individuals with type 1 diabetes mellitus (T1DM) under real-world conditions. Materials and Methods: A retrospective analysis was conducted on 46 adult patients with T1DM who switched to Gla-300 due to frequent hypoglycemia or inadequate glycemic control. HbA1c, fasting plasma glucose (FPG), daily injection frequency, insulin dose, and hypoglycemia rates were evaluated over a 12-month period. Results: A significant reduction in HbA1c (from 8.45±1.27% to 7.83±1.01% at 3 months, p<0.001) and FPG levels was observed. Injection frequency decreased, particularly in patients previously on detemir or neutral protamine hagedorn. Despite a statistically significant increase in basal insulin dose over time, the frequency of all hypoglycemia subtypes declined, with the most prominent reduction in nocturnal hypoglycemia (p<0.001). No severe hypoglycemia occurred after the third month. No cases of ketosis or hospitalizations were reported. The majority of improvements occurred within the first 3 months and were maintained throughout the follow-up. Conclusion: In real-life clinical practice, switching to Gla-300 provided improved glycemic control and reduced hypoglycemia risk in adults with T1DM, particularly in those previously using multiple daily injections. Considering the limited national data and frequent use of older basal insulins in Türkiye, these findings support the potential value of Gla-300 as an alternative option in individualized treatment planning for T1DM.